INCURSIONS ABOUT OPEN EVALUATION - Garcia, Joana Coeli Ribeiro (2021)
It focuses on the creation of the scientific journal and the 16th century when knowledge was discussed in the public arena (open review) and by decision of the inquisitors (evaluators) the authors were imprisoned until they changed (or not) their minds. The periodical was first handed over to book publishers who accepted the intent as it approached its socialization, the expansion in economically profitable quantity until it was sponsored by commercial and university publishers. In this journey, the idea of blind review arises and consolidates. Although open science has from the 20th and 21st centuries onwards technologies can be able to help science solve problems: making communication between individuals faster; knowledge available for scientific records; transformations of scientific records stored and consulted, and open access, the open review that would offer more qualification, has not yet conquered space in scientific review that would offer more qualification, has not yet conquered space in scientific communication, despite editors, authors and reviewers defending it. Evaluation in an open system suits science in this condition, although there is no unanimity in scientific communication about the possibility of widespread use of open peer review (OPR). This article encourages and supports arguments, not necessarily providing all the answers, reaching the objective in favor of open evaluation, in modern times.